2016
DOI: 10.1152/ajprenal.00431.2015
|View full text |Cite
|
Sign up to set email alerts
|

Loss of diacylglycerol kinase epsilon in mice causes endothelial distress and impairs glomerular Cox-2 and PGE2production

Abstract: Thrombotic microangiopathy (TMA) is a disorder characterized by microvascular occlusion that can lead to thrombocytopenia, hemolytic anemia, and glomerular damage. Complement activation is the central event in most cases of TMA. Primary forms of TMA are caused by mutations in genes encoding components of the complement or regulators of the complement cascade. Recently, we and others have described a genetic form of TMA caused by mutations in the gene diacylglycerol kinase-ε (DGKE) that encodes the lipid kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Recently, some groups reported that mutation in the DGKε gene caused kidney disiase 34, 35 . Moreover, it was also reported that the DGKε deficient mice showed multiple glomerular failures and that damage to morphology of normal podocyte 36 . Indeed, DGKε deficient mice have an increased severity of albuminuria by nephrotoxic serum which induces nephritis 36 .…”
Section: Discussionmentioning
confidence: 93%
“…Recently, some groups reported that mutation in the DGKε gene caused kidney disiase 34, 35 . Moreover, it was also reported that the DGKε deficient mice showed multiple glomerular failures and that damage to morphology of normal podocyte 36 . Indeed, DGKε deficient mice have an increased severity of albuminuria by nephrotoxic serum which induces nephritis 36 .…”
Section: Discussionmentioning
confidence: 93%
“…The original report showed that there were no major abnormalities with these animals (see Section Post-translational Modifications of DGKε Proteins; Rodriguez de Turco et al, 2001 ). The renal phenotype of this mouse model was recently re-evaluated in more detail: the animals developed mild signs of renal disease with age (Zhu et al, 2016 ). Interestingly, glomerular lesions were noted in Dgkε-null mice after exposure to doses of nephrotoxic serum that did not affect wild type littermates (Zhu et al, 2016 ).…”
Section: Relationship To Diseasementioning
confidence: 99%
“…The renal phenotype of this mouse model was recently re-evaluated in more detail: the animals developed mild signs of renal disease with age (Zhu et al, 2016 ). Interestingly, glomerular lesions were noted in Dgkε-null mice after exposure to doses of nephrotoxic serum that did not affect wild type littermates (Zhu et al, 2016 ). Mouse models of aHUS often require exposure to exogenous triggers to reveal their pathogenic potential (Pickering et al, 2006 ; Thurman et al, 2012 ; Vernon et al, 2016 ).…”
Section: Relationship To Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…2 DGKE knockout mice have no apparent renal phenotype, but have subclinical abnormalities of the glomerular endothelium and basement membrane on EM, develop glomerular capillary occlusion when exposed to nephrotoxic serum, and have impaired production of cyclooxygenase 2 and prostaglandin E 2 . 13 Currently, DGKE nephropathy manifesting in aHUS has been reported in 35 individuals 1,14-19 and a nephrotic syndrome/MPGN-like phenotype in 9 individuals. 2 The collective characteristics were summarized recently by Azukaitis et al, 19 although without a detailed investigation of reported pathological diagnoses.…”
mentioning
confidence: 99%